Guidelines for nurse managers to promote the competence levels of professional nurses in utilising the electronic system for staffing of agency nurses, in public hospitals in the Western Cape - Van As, Martha Maria (University of Western Cape, 2019)
Magister Curationis - MCur === In 2011, a structured electronic system for the staffing of agency nurses was implemented in the Western Cape as part of the Nursing Information Management System (NIMS). This electronic system was developed to ensure a fair tendering process for the procurement of agency staff, providing information on agency expenditure, maximum wage rates and adherence to principles and rules of supply chain management. Although technology is used more and more in healthcare services within the Western Cape, some professional nurses could lack the skills needed to implement the electronic system appropriately. A descriptive and quantitative design was followed to determine the competence levels of professional nurses in utilising the electronic staffing system for agency nurses in public hospitals in the Metropole, Western Cape. The aim of the study was to develop guidelines for nurse managers according to which they can train professional nurses in hospitals to utilise the electronic system for staffing of agency nurses. Assumptions were adapted from the theoretical framework of Benner (1984) on different levels of competencies and used as theoretical departure of the study. The accessible population for this study was all the professional nurses in hospitals within the Metropole of the Western Cape Government Health registered as users on the database, called the Nursing Information Management System (NIMS) (N=278). This population served as the total inclusive sample for the study. The method of data collection was a self-administered structured questionnaire. The data was analysed by using the SPSS Version 24 software program and descriptive and inferential statistics were conducted.